HUBUNGAN PENERAPAN SOP SERVIS RINGAN (TUNE UP) SEPEDA MOTOR TERHADAP KINERJA MEKANIK BENGKEL DI JAKARTA - F. Supriadi; V. Faiz Akbar; Adi Tri Tyassmadi (Jurnal Konversi Energi dan Manufaktur, 2022)
This study aims to determine the relationship of the application of light motor service SOP (tune-up) to Workshop mechanical performance in Jakarta. This study was conducted at 15 Workshop in Jakarta as representatives with data obtained from 45 mechanics and how big is the relationship of motorcycle tune-up service to mechanical performance. This research is a quantitative descriptive research method with regression and correlation. In this research, the percentage of application of service SOP as an independent variable and mechanical performance as a dependent variable. In this study using 45 respondents mechanics, the 45 mechanics will be a sample of research. The data collection method used is by the method of filling the questionnaire (form) on the independent variable is the percentage of application of SOP service and documents for the dependent variable is the mechanical performance. From the results of the research, it is evident that the variable (x) has a relationship to the variable (y) that is equal to 14.54% and the rest can be obtained from other factors. And between the variable (x) and the variable (y) has a positive relationship, ie the resulting value will be directly proportional.